2002
DOI: 10.1021/jp0142278
|View full text |Cite
|
Sign up to set email alerts
|

Diameter-Controlled Synthesis of Carbon Nanotubes

Abstract: Nearly monodisperse iron nanoclusters have been used to define the diameters of carbon nanotubes grown by chemical vapor deposition (CVD). Iron nanoparticles with average diameters of 3, 9, and 13 nm were used to grow carbon nanotubes with average diameters of 3, 7, and 12 nm, respectively. Transmission electron microscopy studies of the nanotubes show that the as-grown nanotubes are single-walled carbon nanotubes (SWNTs) or thin multiwalled carbon nanotubes (MWNTs) with 2 or 3 layers. Investigations of the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
556
2
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 762 publications
(587 citation statements)
references
References 24 publications
17
556
2
2
Order By: Relevance
“…Traditionally, the most common route to achieve high chiral selectivity is through control of catalyst size due to the reported correlation between catalyst size and resulting nanotube diameter [8][9][10]. For catalyst of similar size, we have previously shown the chemical composition M x 1 M y 2 of binary metal oxide nanoparticles has a significant control over the range of chiralities grown [11].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, the most common route to achieve high chiral selectivity is through control of catalyst size due to the reported correlation between catalyst size and resulting nanotube diameter [8][9][10]. For catalyst of similar size, we have previously shown the chemical composition M x 1 M y 2 of binary metal oxide nanoparticles has a significant control over the range of chiralities grown [11].…”
Section: Introductionmentioning
confidence: 99%
“…This condition is due to nanoparticles activated by their diameter under a given carbon feeding rate where large particles are underfed and not nucleating growth, while smaller particles are cutoff from carbon supplies in consequence of carbon poisoning. [29,30] In this work, Co catalyst has a better role in growing CNTs as compared with Ni due to the effect of catalytic activity. The growth rate of nanotube appears to be more prominent in Co catalyst due to broader particle size distribution that allows further absorption of carbon feedstock, thereby resulting in a much thicker nanotube formation and higher growth rate.…”
Section: Resultsmentioning
confidence: 96%
“…For example, Lieber et al recently reported on the synthesis of SWNTs from pre-made mono-MNPs. 43 No structural information was available on those mono-MNPs. They found that only a small number of the nanoparticles participated in the catalytic process.…”
Section: Results On Other Mono Systemsmentioning
confidence: 99%
“…Other results have also confirmed that monodisperse MNPs are catalytically unequal. 43,45 It is unclear based on the current studies as to what is the key to the initiation of SWNT growth. Some catalysts are capable of producing SWNTs, while others are not.…”
Section: Discussionmentioning
confidence: 96%